Giving fruits and vegetables a tax break: lessons from a Dutch attempt - Luc L Hagenaars; Tera L Fazzino; Joreintje Dingena Mackenbach (Cambridge University Press, 2024)
Abstract Objective: Food taxation can improve diets by making unhealthy foods more expensive and by making healthy foods cheaper. In the Netherlands, a political window of opportunity arose in December 2021 to reduce the value-added tax (VAT) on fruits and vegetables to zero percent. The policy is now facing institutional friction along several fronts, however, delaying and potentially averting its implementation. We analysed this institutional friction to inform future food tax policies. Design: We qualitatively analysed open-access fiscal and health experts' position papers about benefits and downsides of the zero-rate that were discussed with members of parliament in June 2023. Setting: The Netherlands. Participants: Not applicable. Results: Health and fiscal experts expressed noticeably different viewpoints towards the utility of the zero-rate. One important argument fiscal experts based their negative advice upon pertained to the legal restrictions for distinguishing between healthier and unhealthier forms of fruits and vegetables (i.e. the principle of neutrality). A zero-rate VAT on unhealthier forms of fruits and vegetables, e.g. processed cucumber, mixed with salt and sugar, would be undesirable, but differentiating between raw and processed cucumber would offend the neutrality principle. Conclusions: The Dutch attempt to give fruits and vegetables a tax break highlights the need for crystal-clear food classifications when designing food tax policies. Public health nutritionists should combine classifications based on caloric density, palatability, degree of processing and nutrient content to provide a database for evidence-informed tax differentiation according to food item healthfulness.